Patent challenges and factors associated with successful patent challengers under the patent linkage system: recent evidence from South Korea after the Korea United States free trade agreement - Kyung-Bok Son; Nahye Choi; Boram Lee; Joonsoo Byun; Dong-Wook Yang; Tae-Jin Lee (BMC, 2021)
Abstract Objectives The patent linkage system upgraded patent challenges to an important factor in granting timely market approval for generic drugs. We aim to understand patent challenges and identify the factors that are associated with successful patent challengers under the patent linkage system in South Korea. Methods We constructed a novel dataset that combined information on manufacturers with detailed data about their patent challenges after introduction of the patent linkage system. Based on the number of successful patent challenges, manufacturers were categorized into non-challengers, passive challengers, and aggressive challengers. Then, two types of logistic models were applied to identify the factors associated with successful and aggressive challengers. Findings Only 39 active ingredients were challenged by 77 manufacturers from March 2015 to December 2019. Of 171 manufacturers, 94 (55 %) were non-challengers, 58 (34 %) were passive challengers who had succeeded in fewer than 4 patent challenges, and 19 (11 %) were aggressive challengers who had succeeded in 4 or more patent challenges. Higher sales, more employees, and a greater number of reimbursed drugs were associated with being a patent challenger, while a greater number of reimbursed drugs was associated with being an aggressive challenger. Conclusion Some manufacturers utilize patent challenges to strengthen their product portfolios in the market. However, under the patent linkage system, the frequency of patent challenges is limited in South Korea compared to the United States. In particular, patent challenges against drugs in injection form and biologics are very rare.